2009
DOI: 10.1007/s00401-009-0594-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma phosphorylated-TDP-43 protein levels correlate with brain pathology in frontotemporal lobar degeneration

Abstract: In the present study, we have correlated plasma TDP-43 levels, as measured by ELISA, with the presence of TDP-43 pathological changes in the brains of 28 patients with frontotemporal lobar degeneration (FTLD) (14 with FTLD-TDP and 14 with FTLD-tau) and 24 patients with pathologically confirmed AD (8 with, and 16 without, TDP-43 pathological changes). Western blotting revealed full-length TDP-43, including a phosphorylated form, and a phosphorylated Cterminal fragment, in all samples examined. Both ELISA and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 33 publications
0
62
0
2
Order By: Relevance
“…When detected with phospho-independent antibody, plasma TDP-43 level is not significantly different between FTLD and AD, with or without TDP-43 pathology; when detected with phospho-dependent antibody, plasma TDP-43 level is higher in patients with TDP-43 pathology than in those without TDP-43 pathology in FTLD, but this phenomenon is not found in AD patients [44]. Recent study finds that the concentration ratio of TDP-43 CSF to blood is about 1:200, suggesting that CSF TDP-43 may originate from blood [45].…”
Section: Plasma and Csf Levels Of Tdp-43 In Admentioning
confidence: 52%
See 1 more Smart Citation
“…When detected with phospho-independent antibody, plasma TDP-43 level is not significantly different between FTLD and AD, with or without TDP-43 pathology; when detected with phospho-dependent antibody, plasma TDP-43 level is higher in patients with TDP-43 pathology than in those without TDP-43 pathology in FTLD, but this phenomenon is not found in AD patients [44]. Recent study finds that the concentration ratio of TDP-43 CSF to blood is about 1:200, suggesting that CSF TDP-43 may originate from blood [45].…”
Section: Plasma and Csf Levels Of Tdp-43 In Admentioning
confidence: 52%
“…Plasma TDP-43 in AD Elevated plasma TDP-43 level is shown in 46 % of FTLD and 22 % of AD cases, compared to 8 % of control subjects, which closely corresponds to the autopsy-confirmed proportion of TDP-43 pathology in their brain [43,44]. When detected with phospho-independent antibody, plasma TDP-43 level is not significantly different between FTLD and AD, with or without TDP-43 pathology; when detected with phospho-dependent antibody, plasma TDP-43 level is higher in patients with TDP-43 pathology than in those without TDP-43 pathology in FTLD, but this phenomenon is not found in AD patients [44].…”
Section: Plasma and Csf Levels Of Tdp-43 In Admentioning
confidence: 76%
“…In patients with GRN mutations, plasma progranulin level can predict the presence of a mutation and may be an easier and more costeffective screening method (Coppola et al 2008;Ghidoni et al 2008;Finch et al 2009). Preliminary studies looking at plasma TDP-43 levels have unfortunately not shown that they are able to differentiate between different subgroups (Foulds et al 2008;Foulds et al 2009), but further work continues in this area.…”
Section: Bloodmentioning
confidence: 95%
“…[29][30][31][32] However, the interpretation of those results warrants caution, because we found that general organs exhibited TDP-43 accumulation even in individuals without ALS. Copyright of Neuropathology is the property of Wiley-Blackwell and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission.…”
mentioning
confidence: 65%